Palaeoart of the Ice Age. - Bednarik, Robert G. (Cambridge Scholars Publishing, 2017)
The many hundreds of books and thousands of academic papers on the topic of Pleistocene (Ice Age) art are limited in their approach because they deal only with the early art of southwestern Europe. This is the first book to offer a comprehensive synthesis of the known Pleistocene palaeoart of six continents, a phenomenon that is in fact more numerous and older in other continents. It contemplates the origins of art in a balanced manner, based on reality rather than fantasies about cultural primacy. Its key findings challenge most previous perceptions in this field and literally re-write the di.